How to Commercialise Research in Biotechnology? Effectiveness of the Innovation Process and of Technology Transfer in the Biotechnology Sector - Uecke, Oliver; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Biotechnology is considered as a key technology of the 21st century with the potential to offer technological solutions for global health and resource-based problems. Oliver Uecke analyses how early stages of the innovation process in biotechnology can be effectively managed, with the aim to transfer an innovation from academia to industry. A mixed method approach is applied with a multiple case study approach to identify characteristics for effective management and the method of discrete choice experiments/best-worst scaling to estimate the importance of these characteristics. This study adds to existing research by identifying a group of five important characteristics that should be considered for effective management, compared to a group of four characteristics that are less important.
Research gap and contribution -- Definition of key concepts -- The biotechnology sector as conceptual framework -- Data and methodology -- Results, discussion and implications.
Keywords: Economics; Entrepreneurship; Economics/Management Science; Entrepreneurship